Mobiles find right price for farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Mobiles find right price for farmers, BBC, October 2002 Browsing web pages using a mobile phone is catching on among market traders in Senegal.